Predictive Utility of Mortality by Aging Measures at Different Hierarchical Levels and the Response to Modifiable Life Style Factors: Implications for Geroprotective Programs - Zhang, Jingyun; Cao, Xingqi; Chen, Chen; He, Liu; Ren, Ziyang; Xiao, Junhua; Han, Liyuan; Wu, Xifeng; Liu, Zuyun (Frontiers in Medicine, 2022)
Background: Aging, as a multi-dimensional process, can be measured at different hierarchical levels including biological, phenotypic, and functional levels. The aims of this study were to: 1) compare the predictive utility of mortality by three aging measures at three hierarchical levels; 2) develop a composite aging measure that integrated aging measures at different hierarchical levels; and 3) evaluate the response of these aging measures to modifiable life style factors. Methods: Data from National Health and Nutrition Examination Survey 1999-2002 were used. Three aging measures included telomere length (TL, biological level), Phenotypic Age (PA, phenotypic level), and frailty index (FI, functional level). Mortality information was collected until Dec. 2015. Cox proportional hazards regression and multiple linear regression models were performed. Results: A total of 3249 participants (20-84 years) were included. Both accelerations (accounting for chronological age) of PA and FI were significantly associated with mortality, with HRs of 1.67 (95% confidence interval [CI] = 1.41-1.98) and 1.59 (95% CI = 1.35-1.87), respectively, while that of TL showed nonsignificant associations. We thus developed a new composite aging measure (named PC1) integrating the accelerations of PA and FI, and demonstrated its better predictive utility relative to each single aging measure. PC1, as well as the accelerations of PA and FI, were responsive to several life style factors including smoking status, body mass index, alcohol consumption, and leisure-time physical activity. Conclusion: This study demonstrates that both phenotypic (i.e., PA) and functional (i.e., FI) aging measures can capture mortality risk and respond to modifiable life style factors, despite their inherent differences. Furthermore, the PC1 that integrated phenotypic and functional aging measures outperforms in predicting mortality risk in comparison with each single aging measure, and strongly responds to modifiable life style factors. The findings suggest the complementary of aging measures at different hierarchical levels and highlight the potential of life style-targeted interventions as geroprotective programs.